Media outlets in Vojvodina and Slovenia: demographic-economic indicators and media pluralism - Gruhonjić, Dinko A; Milinkov, Smiljana; Katić, Miloš (Geographica Pannonica, 2021)
The paper analyzes the relationship between demographic-economic indicators in the Autonomous Province of Vojvodina and the Republic of Slovenia. Both societies have relatively organized regulatory and political frameworks for the development of media pluralism. It has been established that there is a clear cause-effect relation between the number of media outlets in certain local self-governments and the average net salary: the municipalities and towns with the highest average salaries also boast the highest number of media outlets. However, our analysis has shown that the criteria and mechanisms for identifying risks to media pluralism are not provided: the variety of population representing different political, ideological, cultural and social groups and the variety of interests and standpoints relevant to the local and regional community.
Keywords: media outlets; economics; demography; pluralism